Safety, reliability and risk management an integrated approach - Cox, Sue, Prof (Butterworth-Heinemann, 1998)
Examines the concepts of systems reliability and the techniques available for determining both 'technical' and 'human' hazards and risks. Emphasis is placed both on technical systems and human factors, and the increasing importance of psychological factors in the overall assessment of safety.
Keywords: Industrial safety -- Management.; Risk assessment.; elektronické knihy; electronic books